Workload Analysis in Determining the Number of Workers Handling Delivery of Brake Master Cylinder Products at Company X - Sesmaro Max Yuda; Rocky Rocky; Dikky Antonius (Universitas Sultan Ageng Tirtayasa, 2024)
Company X is one of the largest automotive companies engaged in manufacturing in Indonesia. In company X, there is a section for shipping finished goods/products called the handling delivery section. In this research, a time study was carried out using the stopwatch time study method to obtain standard time, workload, and number of workers to complete the delivery handling process. From the analysis results, it was found that the average working time for PMH hand pallet activities was 327.92 seconds, and PMH forklift was 167.623 seconds. Then, based on working time/worker/day of 420 minutes or 25,200 seconds, with 438 product deliveries per day, the workload of five workers experienced an excess of PMH hand pallet 113.991% and PMH forklift 145.67%. With the addition of one worker for PMH hand pallet, and one worker for PMH forklift, the workload is not excessive, namely 94.99% for PMH hand pallet and 97.10% for PMH forklift.